High, Wide, and Frightened - Thaden, Louise McPhetridge, 1905-1979 (Book collections on Project MUSE., 2004)
Louise Thaden wrote High, Wide, and Frightened in the prime of her life, making this autobiography unique among books about the Golden Age of Aviation. Thaden, a contemporary of Amelia Earhart, was part of a small group of determined women who overcame discrimination and obstacles to become pilots in a time when air races and distance, altitude and endurance records were daily news in America. She became the first woman to win the Bendix Transcontinental Air Race, the premier air race of the day and, before her, a male-dominated one. High, Wide, and Frightened is the story of Thaden's life, of her achievements in aviation, and also of her childhood in Arkansas. She writes about her everyday personal life and her day-to-day experiences in aviation. - Publisher.